Copper-based metal material for green ethylene synthesis as well as preparation method and application of copper-based metal material
Through the preparation and application of copper-based metal materials, the problems of large energy consumption and environmental pollution in traditional ethylene production are solved, the selectivity and activity of ethylene are improved, and the efficient conversion of carbon dioxide into ethylene reaction is achieved.
Patent Information
- Application Number
- CN202411446243.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-14
Smart Images

Figure CN119307967A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of electrochemical technology, and specifically relates to a copper-based metal material for green ethylene synthesis and a preparation method and application thereof. Background Art
[0002] With the increase in global energy demand and the increasing depletion of fossil fuel resources, how to develop clean and sustainable energy technologies has become a major challenge facing the world today. At the same time, the threat of global warming and climate change has also prompted countries to increase their efforts to reduce greenhouse gas emissions. Carbon dioxide is one of the main greenhouse gases. Therefore, the development and utilization of carbon dioxide technology can not only reduce emissions, but also achieve carbon recycling, which is one of the current research hotspots.
[0003] Ethylene, a synthetic chemical, plays an important role in industrial production and is widely used in plastics, rubber, solvents and other fields. However, the traditional ethylene production process mainly relies on fossil fuels such as oil and natural gas, which has the problems of high energy consumption and serious environmental pollution. Therefore, it is particularly important and urgent to find a new method that can efficiently synthesize ethylene and utilize waste carbon dioxide.
[0004] At present, the products of electrochemical reduction of carbon dioxide are mainly carbon monoxide, formic acid, methanol, etc., and the catalytic materials for converting carbon dioxide into hydrocarbons with higher energy density (such as methane, ethylene, ethane, etc.) are still very scarce. In particular, the conversion of carbon dioxide into ethylene requires specific electrolyte and electrode conditions, and the selectivity and yield of ethylene are optimized by adjusting parameters such as current density, temperature and catalyst. At present, the selectivity and activity of electrochemical catalytic reduction of carbon dioxide to produce ethylene are relatively low, and the synthesis process of the catalyst is complicated. Summary of the invention
[0005] The present disclosure aims to solve at least one of the technical problems existing in the prior art and to provide a copper-based metal material for green ethylene synthesis and a preparation method and application thereof.
[0006] In one aspect of the present disclosure, a method for preparing a copper-based metal material for green ethylene synthesis is provided, the preparation method comprising:
[0007] uniformly mixing urea and Cu(NO3)2 to obtain a mixture;
[0008] The mixture was transferred into a crucible, pyrolyzed under an argon atmosphere, and then cooled to room temperature to obtain a Cu / Cu2O-C catalyst.
[0009] Optionally, the content of urea is 5 to 15 parts by mass;
[0010] The content of Cu(NO3)2 is 0.01 to 0.05 parts by mass.
[0011] Optionally, urea and Cu(NO3)2 are uniformly mixed to obtain a mixture comprising:
[0012] Mix urea and Cu(NO3)2, and perform ball milling for 0.5-1.5h to obtain a mixture.
[0013] Optionally, the pyrolysis temperature is 600-800° C., and the pyrolysis time is 0.5-1.5 h.
[0014] Optionally, during the pyrolysis process, the heating rate is 5°C / min.
[0015] In another aspect of the present disclosure, a copper-based metal material for green ethylene synthesis is provided, wherein the copper-based metal material is prepared by the preparation method described above.
[0016] Optionally, the copper-based metal material is in a three-dimensional structure of spherical stacking.
[0017] Optionally, the copper-based metal material has a diameter of 10 nm to 2 μm.
[0018] In another aspect of the present disclosure, a copper-based metal material as described above is provided for use in an electrode for electrochemical reduction of carbon dioxide to synthesize ethylene.
[0019] Optionally, the application process includes:
[0020] The copper-based metal material is added into a mixed solution of tetrahydrofuran, 2-propanol and Nafion perfluororesin solution, and subjected to ultrasonic treatment to form a mixed suspension;
[0021] The mixed suspension is dropped onto the surface of the electrode substrate to obtain an electrode.
[0022] The present disclosure proposes a copper-based metal material for green ethylene synthesis and a preparation method and application thereof, wherein the preparation method of the copper-based metal material comprises: uniformly mixing urea and Cu(NO3)2 to obtain a mixture; transferring the mixture to a crucible, pyrolyzing it under an argon atmosphere, and then cooling it to room temperature to obtain a Cu / Cu2O-C catalyst. The present disclosure uses an in-situ synthesis method, wherein urea is used as a carbon source precursor during the preparation process, and high-temperature treatment is performed under an inert environment, thereby achieving a one-step synthesis of a carbon-doped copper-based metal material. The preparation process is simple, the required raw materials are simple, and the cost is low. In addition, the obtained copper-based metal material can promote the conversion of carbon dioxide into ethylene, thereby improving the selectivity and activity for ethylene. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1This is a flowchart of a method for preparing a copper-based metal material according to an embodiment of the present disclosure;
[0024] Figure 2 A flowchart of forming an electrode material from a copper-based metal material according to another embodiment of the present disclosure;
[0025] Figure 3 This is a scanning electron microscope image of the copper-based metal material of Example 1 of the present disclosure;
[0026] Figure 4 This is a transmission electron microscope image of the copper-based metal material of Example 1 of the present disclosure;
[0027] Figure 5 This is a graph showing the ethylene conversion efficiency-voltage curve of Example 1 of the present disclosure. DETAILED DESCRIPTION
[0028] In order to enable those skilled in the art to better understand the technical solution of the present disclosure, the present disclosure is further described in detail below in conjunction with the accompanying drawings and specific implementation methods. It should be understood that the specific embodiments described herein are only used to explain the present disclosure and are not used to limit the disclosure. The described embodiments are part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the described embodiments of the present disclosure, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present disclosure.
[0029] like Figure 1 As shown, in one aspect of the present disclosure, a method S100 for preparing a copper-based metal material for green ethylene synthesis is provided, comprising steps S110 to S120:
[0030] S110, uniformly mix urea and Cu(NO3)2 to obtain a mixture.
[0031] Specifically, urea powder is mixed with Cu(NO3)2 and subjected to ball milling for 0.5 to 1.5 hours.
[0032] A mixture is obtained. Of course, in other preferred embodiments, the two components can also be mixed in other ways, which are not specifically limited.
[0033] In some preferred embodiments, the ball milling time is 0.5 h, 1 h, 1.5 h, etc.
[0034] In other preferred embodiments, the content of urea is 5 to 15 parts by mass, for example, 5 parts by mass, 7 parts by mass, 10 parts by mass, 12 parts by mass, 15 parts by mass, etc.
[0035] As a further preferred embodiment, the content of urea is preferably 10 parts by mass.
[0036] In other preferred embodiments, the content of Cu(NO3)2 is 0.01 to 0.05 parts by mass, for example, 0.01 parts by mass, 0.02 parts by mass, 0.03 parts by mass, 0.04 parts by mass, 0.05 parts by mass, etc.
[0037] As a further preferred embodiment, the content of urea is preferably 0.018 parts by mass, and the corresponding amount of the substance is preferably 0.1-0.2 mmol, for example, 0.1 mmol.
[0038] S120, transferring the mixture into a crucible, pyrolyzing it under an argon atmosphere, and cooling it to room temperature to obtain a Cu / Cu2O-C catalyst.
[0039] It should be noted that the pyrolysis process has a great influence on the improvement of the catalytic activity of the material. Different pyrolysis temperatures will result in different catalyst activities. Therefore, the choice of pyrolysis temperature is also crucial.
[0040] In some preferred embodiments, the pyrolysis temperature is 600-800°C, and the pyrolysis time is 0.5-1.5 hours. In addition, during the pyrolysis process, the heating rate is 5°C / min. That is, the temperature is increased to 700°C at 5°C / min, and the temperature is maintained at 700°C for 0.5-1.5 hours.
[0041] In this embodiment, urea is used as a carbon source to form a carbon-doped copper-based metal catalytic material. The material has a spherical stacking structure to form a three-dimensional structure with more active sites for adsorbing a large amount of carbon dioxide and promoting its conversion into ethylene.
[0042] Another aspect of the present disclosure provides a copper-based metal material for green ethylene synthesis. The copper-based metal material is prepared by the preparation method described above. Please refer to the above description for the specific process, which will not be repeated here.
[0043] Combined Figure 3 As shown, the copper-based metal material of this embodiment is a three-dimensional structure of spherical stacking, with a diameter ranging from tens of nanometers to several micrometers. For example, in some preferred embodiments, the diameter of the copper-based metal material is 10nm to 2μm.
[0044] Combined Figure 4 As shown, the diameter of the Cu / Cu2O nanoparticles is about 10 nm, showing two crystalline phases of Cu(200) and Cu2O(111).
[0045] In another aspect of the present disclosure, a copper-based metal material as described above is provided for use in an electrode for electrochemical reduction of carbon dioxide to synthesize ethylene.
[0046] Furthermore, if Figure 2As shown, the specific application process S200 includes the following steps S210 to S220:
[0047] S210, adding a copper-based metal material to a mixed solution of tetrahydrofuran, 2-propanol and Nafion perfluororesin solution, and subjecting the mixture to ultrasonic treatment for 30 minutes to form a mixed suspension;
[0048] In some preferred embodiments, the solid-to-liquid ratio of the catalyst to tetrahydrofuran, 2-propanol, and Nafion perfluororesin solution is 1:(85-95):(95-100):(10-11) mg / μL, for example, 1:90:100:10, etc.
[0049] As a further preferred embodiment, the content of the catalyst may be preferably 4-6 mg, and correspondingly, the content of tetrahydrofuran may be preferably 400-500 mL, the content of 2-propanol may be preferably 450-550 mL, and the content of Nafion perfluororesin solution may be preferably 45-55 mL.
[0050] As a further preferred embodiment, the content of the catalyst may be preferably 5 mg, and correspondingly, the content of tetrahydrofuran may be preferably 450 mL, the content of 2-propanol may be preferably 500 mL, and the content of Nafion perfluororesin solution may be preferably 50 mL.
[0051] It should be noted that the Nafion perfluorinated resin solution can be a Nafion perfluorinated resin solution with a concentration of 5 wt %, which can further improve the carbon dioxide capture capability. In addition, the component also has good electrical conductivity and low resistivity, and can maintain good chemical stability.
[0052] S220, dropping the mixed suspension onto the surface of the electrode substrate to obtain an electrode.
[0053] It should be noted that the present embodiment does not specifically limit the manner in which the suspension is added dropwise to the surface of the electrode substrate. For example, the suspension is added dropwise to the surface of the electrode substrate so that the suspension is more evenly coated on the electrode.
[0054] When the copper-based metal material catalyst of this embodiment is used in the electrochemical reduction of carbon dioxide, the electric current in the electrolytic cell is used to act on the electrolyte solution containing carbon dioxide, and the carbon dioxide is converted into ethylene through a reduction reaction. The copper-based metal material promotes the reduction of carbon dioxide and hydrogen ions to produce ethylene and water, effectively improving the yield and selectivity of ethylene.
[0055] It should be further explained that the present embodiment does not specifically limit the type of the electrode substrate, for example, carbon paper, carbon cloth, carbon felt, etc.
[0056] In some preferred embodiments, the carbon paper may preferably be AvCarb MGL190, MGL370, MGL280, and the like.
[0057] It should be noted that the present embodiment does not specifically limit the size of the electrode substrate, for example, 1×1 cm 2 Of course, for those skilled in the art, other sizes of base materials can also be set.
[0058] The preparation method and application of copper-based metal materials will be further explained below in conjunction with several specific examples:
[0059] Example 1
[0060] The method for preparing the copper-based metal material in this example includes the following steps:
[0061] S1. Weigh 10 g of urea powder and 0.1 mmol of Cu(NO3)2, and ball mill for 1 h to mix them evenly.
[0062] S2. The mixture was transferred to a crucible and pyrolyzed in an argon atmosphere under the following conditions: heating to 700°C at a rate of 5°C / min, maintaining the temperature at 700°C for 1 h, and cooling to room temperature to obtain a Cu / Cu2O-C catalyst.
[0063] Furthermore, in this embodiment, a scanning electron microscope is used to characterize the microscopic morphology of the copper-based metal material, such as Figure 3 As shown, the prepared Cu / Cu2O-C presents a three-dimensional structure, and the formed spherical structures are stacked with diameters ranging from tens of nanometers to several microns.
[0064] Furthermore, this embodiment also uses transmission electron microscopy to characterize the size and distribution of the material, such as Figure 4 As shown, the diameter of the Cu / Cu2O nanoparticles is about 10 nm, showing two crystalline phases of Cu(200) and Cu2O(111).
[0065] Furthermore, in this embodiment, the obtained copper-based metal material is coated on the surface of the electrode, and the specific process includes:
[0066] 5 mg of the prepared Cu / Cu2O-C catalyst was added to 450 μL of tetrahydrofuran, 500 μL of 2-propanol and 50 μL of a 5 wt% Nafion perfluororesin mixed solution, and a uniform mixed suspension solution was formed after ultrasonication for 30 minutes. The suspension solution was added dropwise onto AvCarb MGL370 carbon paper (1×1 cm 2 ) surface, thereby preparing the electrode material.
[0067] Furthermore, the present embodiment also uses the electrode material in electrochemistry. The electrochemical test is performed by a three-electrode system, wherein the working electrode is the prepared electrode material, the reference electrode is an Ag / AgCl / sat.KCl electrode, the counter electrode is a Pt mesh, and the electrolyte is a 0.1M KHCO3 solution. The electrochemical CO2 reduction test is performed in a constant current mode. Figure 5 As shown in Table 1, as the potential gradually decreases from -0.2V to -0.6V vs RHE, the electrokinetics gradually improves, and the yield of ethylene also increases accordingly. Among them, under the condition of -0.3V vs RHE, the selectivity of ethylene reaches the maximum, which is 90%. This shows that the Cu / Cu2O-C catalyst of this embodiment is beneficial to promote the conversion of carbon dioxide into ethylene, thereby improving the yield and selectivity of ethylene.
[0068] Example 2
[0069] The method for preparing the copper-based metal material in this example includes the following steps:
[0070] S1. Weigh 10 g of urea powder and 0.1 mmol of Cu(NO3)2, and ball mill for 1 h to mix them evenly.
[0071] S2. The mixture was transferred to a crucible and pyrolyzed in an argon atmosphere under the following conditions: the temperature was increased to 500° C. at a rate of 5° C. / min, maintained at 600° C. for 1 h, and cooled to room temperature to obtain a Cu / Cu2O-C catalyst.
[0072] S3, 5 mg of the prepared Cu / Cu2O-C catalyst was added to 450 μL of tetrahydrofuran, 500 μL of 2-propanol and 50 μL of a 5 wt% Nafion perfluororesin mixed solution, and a uniform mixed suspension solution was formed after ultrasonication for 30 minutes. The suspension solution was added dropwise onto AvCarb MGL370 carbon paper (1×1 cm 2 ) surface, thereby preparing the electrode material.
[0073] As shown in Table 1, the catalytic activity of the catalyst obtained in Example 2 decreased significantly compared with that in Example 1, and the yield of ethylene decreased, which indicates that the catalytic efficiency of the catalyst obtained at a pyrolysis temperature of 500° C. for ethylene is significantly reduced.
[0074] Example 3
[0075] The method for preparing the copper-based metal material in this example includes the following steps:
[0076] S1. Weigh 10 g of urea powder and 0.1 mmol of Cu(NO3)2, and ball mill for 1 h to mix them evenly.
[0077] S2. The mixture was transferred to a crucible and pyrolyzed in an argon atmosphere under the following conditions: heating to 800°C at 5°C / min, maintaining the temperature at 600°C for 1 h, and cooling to room temperature to obtain a Cu / Cu2O-C catalyst.
[0078] S3, 5 mg of the prepared Cu / Cu2O-C catalyst was added to 450 μL of tetrahydrofuran, 500 μL of 2-propanol and 50 μL of a 5 wt% Nafion perfluororesin mixed solution, and a uniform mixed suspension solution was formed after ultrasonication for 30 minutes. The suspension solution was added dropwise onto AvCarb MGL370 carbon paper (1×1 cm 2 ) surface, thereby preparing the electrode material.
[0079] As shown in Table 1, the catalytic activity of the catalyst obtained in Example 3 is slightly lower than that of Example 1, which shows that the catalyst obtained at a pyrolysis temperature of 800° C. still has a good catalytic efficiency for ethylene. In summary, when the pyrolysis temperature is 700° C., the catalytic activity of the copper-based metal material for synthesizing ethylene is optimal.
[0080] Comparative Example 1
[0081] This example is a blank control example. The copper-based metal material is not coated on the electrode surface. The electrode material is directly used in electrochemistry. The results are as follows:
[0082] 450 μL of tetrahydrofuran, 500 μL of 2-propanol and 50 μL of 5 wt% Nafion perfluororesin were mixed and subjected to ultrasound for 30 minutes to form a uniform mixed suspension solution. The suspension solution was added dropwise onto AvCarb MGL370 carbon paper (1×1 cm 2 ) surface, thereby preparing an electrode material, which is used in electrochemistry. The electrochemical test is carried out through a three-electrode system. The electrochemical CO2 reduction test is carried out in constant current mode, and the selectivity of ethylene is only 45%.
[0083] As shown in Table 1, the catalyst obtained in Comparative Example 1 has significantly lower catalytic activity for ethylene than that of Examples 1-3, and thus the yield of ethylene is reduced, which indicates that the copper-based metal material has good selectivity and catalytic activity for the synthesis of ethylene.
[0084] Table 1 Yield of ethylene in each embodiment and comparative example
[0085] Ethylene yield Example 1 90% Example 2 61% Example 3 83% Comparative Example 1 45%
[0086] The present disclosure provides a copper-based metal material for green ethylene synthesis and a preparation method and application thereof, which have the following beneficial effects:
[0087] First, through the in-situ synthesis method, urea is used as a carbon source precursor in the preparation process, and high-temperature treatment is performed under an inert environment to achieve a one-step synthesis of carbon-doped copper-based metal materials. The preparation process is simple, the required raw materials are simple, and the cost is low.
[0088] Second, the copper-based metal material disclosed in the present invention has great activity in the electrochemical CO2 reduction reaction, which helps to convert carbon dioxide into ethylene and effectively improves the synthesis efficiency of ethylene.
[0089] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present disclosure, but the present disclosure is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and substance of the present disclosure, and these modifications and improvements are also considered to be within the scope of protection of the present disclosure.
Claims
1. A method for preparing a copper-based metal material for green ethylene synthesis, characterized in that: The preparation method comprises: uniformly mixing urea and Cu(NO3)2 to obtain a mixture; The mixture was transferred into a crucible, pyrolyzed under an argon atmosphere, and then cooled to room temperature to obtain a Cu / Cu2O-C catalyst.
2. The preparation method according to claim 1, characterized in that: The content of urea is 5 to 15 parts by mass; The content of Cu(NO3)2 is 0.01 to 0.05 parts by mass.
3. The preparation method according to claim 1, characterized in that: The urea and Cu(NO3)2 are uniformly mixed to obtain a mixture comprising: Mix urea and Cu(NO3)2, and perform ball milling for 0.5-1.5h to obtain a mixture.
4. The preparation method according to claim 1, characterized in that: The pyrolysis temperature is 600-800° C., and the pyrolysis time is 0.5-1.5 h.
5. The preparation method according to claim 4, characterized in that: During the pyrolysis process, the heating rate was 5 °C / min.
6. A copper-based metal material for green ethylene synthesis, characterized in that: The copper-based metal material is prepared by the preparation method described in any one of claims 1 to 5.
7. The copper-based metal material according to claim 6, characterized in that: The copper-based metal material is in a three-dimensional structure of spherical stacking.
8. The copper-based metal material according to claim 6, characterized in that: The diameter of the copper-based metal material is 10 nm to 2 μm.
9. An application of a copper-based metal material, characterized in that: The copper-based metal material according to any one of claims 6 to 8 is used in electrodes for electrochemical reduction of carbon dioxide to synthesize ethylene.
10. The use according to claim 9, characterized in that: The application process includes: The copper-based metal material is added into a mixed solution of tetrahydrofuran, 2-propanol and Nafion perfluororesin solution, and subjected to ultrasonic treatment to form a mixed suspension; The mixed suspension is dropped onto the surface of the electrode substrate to obtain an electrode.